SOCIALIZATION OF STUDENT YOUTH IN THE CONDITIONS OF THE INFORMATION AGE (Pedagogy of Higher and Secondary Education, 2011)
In article is devoted to the topical problem - research of pedagogical bases of students' socialization by informational communications. By means of theoretical analysis of scienctife papers here determined the essence and specificity of students' socialization by informational communicationa as the instityte of socialization, students as a special social group.
Keywords: socialization; sociality; the institute of socialization; informational communications